Topology of Project Management Office in United Arab Emirates Project-Based Organizations - Abdulla Ali Abdul Ghani Al Khoori,; Abdul Hamid, Mohd Syaiful Rizal (International Journal of Sustainable Construction Engineering and Technology, 2022)
Majority of projects failed due to mismanagement factors such as funds, planning, time, and resources. With the adoption of Project Management Office (PMO) in an organization, it able to manage the projects practises through a distinctive office dedicated to project management with specific roles and functions that should be followed by the project officer for all the projects. The positioning of PMO in the organisational structure and its job responsibilities, are critical factors in project success. This paper presents a study to uncover the topology of PMO in the project-based organizations in United Arab Emirates (UAE). This qualitative study was conducted through interviews with twenty professionals working in PMO from four companies in the UAE. Based on the findings from the interview sessions, PMOs can be divided into three types: supportive, controlling, and directive. The result indicates that the type of PMO chosen have a significant impact on the efficiency of the project delivery. While controlling PMO approach, it is desired to "clear-house" the activities, processes, procedures, documentation, and more, the organisation requires that the help be used in addition to providing it, supportive PMO is the best choice if the goal is to establish a "rein in" of project management data that all project managers within the firm may freely access. Furthermore, Directive PMO goes beyond simple control and "takes over" projects by providing the necessary resources and project management expertise. According to the findings of the interviews, the PMO performs a variety of functions, including project support, training, lesson-learned maintenance, project management tool and software support, project control, inter-project communication, managing shared resources, and encouraging good project management and decision-making. PMO forecasts future resource requirements, plans for strategic, non-billable, and billable usage, and assigns appropriate resources to appropriate projects at appropriate times. This improves resource utilisation efficiency, and significantly lowers project resource costs.